Distinct supramolecular assemblies of nickel(II) complexes constructed from N-(4-pyridylmethyl)-l-amino acid derivatives: Synergistic effects of substituent groups and counter anions. (1st July 2018) - Zhang, Zhi-Hui; Li, Xiu-Ying; Yang, Xu-Sheng; Chen, Sheng-Chun; Weng, Zhehui; He, Ming-Yang
Graphical abstract: The synergistic effects of substituent groups and counter anions in Ni(II) complexes of reduced Schiff bases result in distinct one- or two-dimensional coordination arrays, but similar three-dimensional hydrogen-bonding assemblies. The coordination interaction between the Ni(II) ion and formate moieties indicates a stronger coordination ability of formate ions than that of acetate ions. Abstract: Four Ni(II) reduced Schiff base complexes, [Ni(L1)(HCOO)(H2 O)](H2 O) (1 ), [Ni(L2)(H2 O)3 ](OAc) (2 ), [Ni(L3)(H2 O)3 ](OAc) (3 ) and [Ni(L4)(HCOO)](H2 O) (4 ), have been synthesized by the reaction of N-(4-pyridylmethyl)-l -amino acid derivatives and Ni(OAc)2 ·4H2 O under hydrothermal conditions. Single-crystal X-ray diffraction analysis reveals all of the four Ni(II) centers in these complexes adopt a six-coordinated octahedral geometry, with complexes 1 –3 uniformly crystallizing in the monoclinic P 21 space group and 4 in the P 21 21 21 space group. A detailed structural study indicates the synergistic effects of the counteranions and steric hindrance of the substituents of the amino ligands lead to the formation of two different dimensionalities of the four compounds, with complexes 1 and 4 featuring 2D layer structures while complexes 2 and 3 exhibiting 1D chain structures. The resulting 3D supramolecular networks are formed by strong hydrogen bonding (OH⋯O and NH⋯O) interactions between the ligands and the guest molecules. The thermal stability, infrared spectra and luminescence properties of these compounds have also been investigated.